Ephemeral Inscriptions: Graffiti, Gentrification, and the Struggle for Public Space in the Indonesian Metropolis - Bimala Putri; Omar Alieva; Henny Kesuma; Ifah Shandy; Ni Made Nova Indriyani (Enigma in Cultural, 2025)
The visual landscape of the contemporary city is a contested terrain where cultural expression and economic forces collide. This study investigates the complex relationship between graffiti practices and gentrification in Indonesia, moving beyond a simple resistance-versus-commodity binary to analyze graffiti as a dialectical force in urban transformation. It examines how graffiti functions as a mode of spatial inscription, a carrier of urban affect, and a critical barometer of the struggle for the right to the city in the Global South. This research employed a longitudinal, mixed-methods, comparative case study design, focusing on the Glok district in Jakarta and the Braga district in Bandung (2019-2025). The methodology integrated quantitative spatio-temporal GIS analysis of 1,250 graffiti pieces correlated with economic data, and a systematic content analysis of their form and themes. This was triangulated with deep qualitative data from 24 months of ethnographic fieldwork and 45 semi-structured interviews with artists, residents, and officials. A critical positionality statement reflects on the ethical praxis of the research. The findings reveal a clear trajectory where illicit, text-based graffiti, initially prevalent in peripheral spaces, created a subcultural "symbolic economy." This was followed by a spatial and formal shift towards large-scale, sanctioned murals in prime commercial zones. Quantitative analysis established a strong correlation (r = 0.78) between mural density and rising commercial rents, but this is interpreted cautiously to avoid assumptions of direct causality. Ethnographic vignettes and interview data reveal the affective dimensions of this transformation, highlighting how the changing streetscape is experienced as a loss of place by long-term residents and consumed as an aesthetic "vibe" by newcomers, while artists navigate complex issues of agency and co-optation. In conclusion, the evolution of graffiti from illicit inscription to curated aesthetic mirrors the process of gentrification. The study concludes that while the co-optation of street art is a powerful force in neoliberal place-branding, the practice remains a site of contested agency and meaning-making. The concept of "ephemeral inscriptions" is proposed to better capture the performative, transient, and deeply political nature of these markings as they chronicle the ongoing struggle for spatial justice.